Controlling impact mitigation via Bouligand nanostructures - Sujin R. Lee; Katherine M. Evans; Jeremiah W. Woodcock; Jan Obrzut; Liping Huang; Christopher L. Soles; Edwin P. Chan (Proceedings of the National Academy of Sciences, 2025)
Critical to their survival, natural organisms have developed exoskeletons that can withstand and inflict damage over their lifetime. The Bouligand structure of the exoskeleton plays a key role in toughness and damage resistance under external impacts. Numerous studies have investigated the morphology of Bouligands and their mechanical properties, yet understanding their structure–function relationship remains challenging due to the complex mechanical responses of biological materials and the limitation of current characterization techniques. Motivated to elucidate the design principles of the natural Bouligand structure for impact mitigation, we conduct impact experiments on synthetic Bouligand films composed of cellulose nanocrystals. By controlling the sonication conditions and evaporation rate of the cellulose nanocrystal suspensions, Bouligand films with controlled variations in pitch and thicknesses are generated. The impact performance and mechanical response of these materials are quantified using a microprojectile-based coefficient of restitution experiments and postimpact damage characterization. Our studies reveal two different energy dissipation mechanisms: plastic deformation and acoustic wave attenuation. The transition in mechanism is governed by the film thickness, the helical pitch dimension, and the moisture content of the film.